2001
DOI: 10.1029/01eo00295
|View full text |Cite
|
Sign up to set email alerts
|

EU‐sponsored effort improves monitoring of circulation variability in the Mediterranean

Abstract: The Mediterranean Sea, bordered by many North African countries and opening eastward to the Black Sea, is a strategic area for Europe. Its coast is one of the most heavily populated regions of the world. A large part of a coastal nation's gross national product is produced through fishing, transportation, recreation, and other industries that depend on a healthy marine coastal environment. The risk of an incident likely to release harmful substances and cause massive pollution is considered high, as the Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 2 publications
(3 reference statements)
1
12
0
1
Order By: Relevance
“…8), reveals that the water column responds to the seasonal variations of the surface fluxes at great depths, causing the winter homogenisation of the waters from the surface down to 100 m depth and the establishment of the strong summer thermocline down to 40-50 m depth. The thermohaline structure simulated by the CYCOM is of particular interest and shows similar water mass distribution, characterizing the study area, such as those found during the renewed in situ observational investigations of the SE Levantine Basin, between 1995-2001 within the frame of the CYBO, CY-CLOPS and MFSPP projects (Zodiatis et al, 1998a;Zodiatis et al, 2001;Manzella et al, 2001). The surface saline waters and the LIW were found to occupy the eastern part of the model domain, while the western part of the model domain is intruded by the MAW, which is transferred in the area by the MMJ.…”
Section: Resultsmentioning
confidence: 99%
“…8), reveals that the water column responds to the seasonal variations of the surface fluxes at great depths, causing the winter homogenisation of the waters from the surface down to 100 m depth and the establishment of the strong summer thermocline down to 40-50 m depth. The thermohaline structure simulated by the CYCOM is of particular interest and shows similar water mass distribution, characterizing the study area, such as those found during the renewed in situ observational investigations of the SE Levantine Basin, between 1995-2001 within the frame of the CYBO, CY-CLOPS and MFSPP projects (Zodiatis et al, 1998a;Zodiatis et al, 2001;Manzella et al, 2001). The surface saline waters and the LIW were found to occupy the eastern part of the model domain, while the western part of the model domain is intruded by the MAW, which is transferred in the area by the MMJ.…”
Section: Resultsmentioning
confidence: 99%
“…4). The assimilation cycle is chosen to be a week, consistent with the XBT data distribution (Manzella et al, 2001) and the SLA data availability .…”
Section: The Data Assimilation Schemementioning
confidence: 99%
“…The XBT data are collected along seven tracks with an along-track spatial nominal resolution of 12 nm (Manzella et al, 2001). Each track was repeated once per month from September 1999 until December 1999 and twice per month from January until June 2000 (with the exception of the track crossing longitudinally all the basin that was made only once a month).…”
Section: Appendix a Near Real Time Data Collection And Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations